1988
DOI: 10.1073/pnas.85.7.2125
|View full text |Cite
|
Sign up to set email alerts
|

Splicing mutation in human hereditary analbuminemia.

Abstract: We have identified a structural defect in the serum albumin gene in human analbuminemia. Sequence determination of 1.1 kilobases (kb) of the 5' regulatory region and of 6 kb across exonic regions revealed a single AG-to-GG mutation within the 3' splice site of intron 6 in the defective gene of an analbuminemic individual. In an in vitro assay on the RNA transcript this mutation causes a defect in splicing of the intron 6 sequence and in subsequent ligation of the exon 6-exon 7 sequences. Using polymerase-ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
37
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 29 publications
1
37
0
Order By: Relevance
“…The mutated gene would have produced a truncated albumin of only 273 residues, but no evidence for this product is available. This mutation differs from the exon splicing defect found in the only other case of human analbuminemia studied at the gene level (17) and from the 7-bp deletion observed in the albumin gene ofNagase analbuminemic rats (18). Further studies with DNA from several other human subjects indicated that each had a different, as yet unidentified, mutation.…”
mentioning
confidence: 83%
See 4 more Smart Citations
“…The mutated gene would have produced a truncated albumin of only 273 residues, but no evidence for this product is available. This mutation differs from the exon splicing defect found in the only other case of human analbuminemia studied at the gene level (17) and from the 7-bp deletion observed in the albumin gene ofNagase analbuminemic rats (18). Further studies with DNA from several other human subjects indicated that each had a different, as yet unidentified, mutation.…”
mentioning
confidence: 83%
“…4). The (17). The putative translation product is presumably truncated by a stop codon at the exon 6/intron 6 junction resulting in a predicted protein product of about 24 kDa compared with 66.5 kDa for normal albumin.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations